Aerodynamic characteristics and flow pattern of a golf ball with rotation - Aoki, K.; Muto, K.; Okanaga, H. (Procedia Engineering, 2010)
The present study investigated the aerodynamic characteristics and flow pattern of a golf ball with 328 circular arc dimples. The aerodynamic forces and the flow pattern around a golf ball were investigated experimentally. The detailed flow pattern around a golf ball was then investigated computationally by Large eddy simulation. The aerodynamic characteristics and the flow pattern of a golf ball with rotation were clarified. In addition, the flying distance was clarified through a flying simulation based on the aerodynamic forces and the flow pattern.